Ozonated Olive Oil Dressing for Pediatric Hypospadias Repair: A Prospective Randomized Clinical Trial - Vincenzo Coppola; Maria Escolino; Fulvia Del Conte; Claudia Di Mento; Francesca Carraturo; Giovanni Esposito; Francesco Tedesco; Roberta Guglielmini; Ciro Esposito (Children)
Many ozone-based products that promote the healing process of wounds have been released in recent years. In this study, we evaluate a new spray dressing preparation based on stable ozonides with Vitamin E Acetate in children operated for distal hypospadias. Methods: We included all patients with distal hypospadias, who underwent Tubularized Incised Plate Urethroplasty (TIPU) over a 12-month period. The patients were randomized in two groups according to the type of medication: ozonide spray with Vitamin E Acetate (G1); hyaluronic acid cream (G2). After discharge, parents changed the dressing twice a day for 2–3 weeks postoperatively. The patients were evaluated at 7, 14, 21, 30, 60, and 180 postoperative days and thereafter annually. At the end of the treatment, we submitted a satisfaction questionnaire to parents. Results: Eighty-six patients (median age 18 months) were included. The wound healing was significantly faster in G1 compared with G2 (p = 0.001). No adverse skin reactions occurred in either group. Foreskin dehiscence and re-operation rates were lower in G1. Postoperative foreskin retractability was better in G1, with a significantly higher incidence of secondary phimosis in G2. The median treatment costs were significantly lower in G1 compared with G2 (p = 0.001). Group 1 found the spray dressing easy to use, improving patient management and adherence. Conclusions: The new preparation of ozonide-based product adopted promoted faster wound healing compared to conventional dressing. Furthermore, this spray preparation is easy to apply, economical, and simpler to preserve. This is better for parents who do not have to touch the wound to apply the product.